2020
DOI: 10.1093/gji/ggaa469
|View full text |Cite
|
Sign up to set email alerts
|

The moderate size 2019 September Mw 5.8 Silivri earthquake unveils the complexity of the Main Marmara Fault shear zone

Abstract: Summary The unbroken section of the North Anatolian Fault beneath the Sea of Marmara is a major source of seismic hazard for the city of İstanbul. The northern and currently the most active branch, the Main Marmara Fault (MMF), is segmented within a shear zone and exhibits both partially creeping and locked behavior along its 150 km length. In September 2019, a seismic activity initiated near MMF, off-coast the town of Silivri, generating 14 earthquakes ≥ Mw3.5 in a week. The Mw5.8 Silivri earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 31 publications
7
31
0
Order By: Relevance
“…Our estimation of 0.75 m as the average source dislocation of the MW5.7 event is larger and in good agreement with the slip range considered in Figure 7 of Karabulut et al (2021). Average source dislocations calculated through Thingbaijam et al (2017) are shown in Table 3 as well.…”
Section: Source Parameterssupporting
confidence: 85%
See 4 more Smart Citations
“…Our estimation of 0.75 m as the average source dislocation of the MW5.7 event is larger and in good agreement with the slip range considered in Figure 7 of Karabulut et al (2021). Average source dislocations calculated through Thingbaijam et al (2017) are shown in Table 3 as well.…”
Section: Source Parameterssupporting
confidence: 85%
“…In the case of 26 th September earthquake, moment magnitudes stated by both organizations are identical with those of KOERI (KOERI-RETMC 2019a& 2019b. The focal mechanism solution of the 24 th September earthquake is compatible with the fault mechanism of NAF's central Marmara segment and exhibits a strike-slip dominancy (KOERI-RETMC 2019a, Karabulut et al 2021). However, there are different views about the faulting mechanism of the 26 September 2019 event.…”
Section: Earthquake Informationmentioning
confidence: 83%
See 3 more Smart Citations